Ontologising social justice in decolonised and post-apartheid settings - Ntshoe, I.M. (South African Journal of Higher Education, 2020)
One topical issue in South Africa since the 1994 democratic elections is how a socially just higher education may be advanced in the context of the decolonial demand for the recognition of diverse epistemologies in the curriculum. The challenge since 1994 however has been what social justice means in the decolonial and post-apartheid settings where injustices continue to be perpetrated on the basis of race, albeit covertly. This article examines African and South African epistemologies and ontologies of social justice, in the context of decoloniality and curricula transformation in higher education, that became more pronounced through the #Feesmustfall protests in 2015. I argue that while social justice occurs within particular historical and political contexts, it is necessary to discern some ontologies of social justice that are not necessarily reducible to contexts. Use is made of Realist (R), Critical Realist (CR) and Race Realist Theory (RRT) perspective to unpack paradoxical constructions of social justice in post-colonial and post-apartheid South Africa.